IDENTIFIKASI DAN KARAKTERISTIK SERUAK DINGIN (COLD SURGE) TAHUN 1995-2003 - Edvin Aldrin; Gilang Satriya Adhi Utama (Jurnal Sains Dirgantara, 2007)
The study identifies the cold suge characteristics that influence the rainfall season in the northwestern part of Indonesia. This study found the cold surge episode to be active and propagate to the equator right after 4 to 6 days of increasing cold surge indices in Hong Kong. The cold surge also interacts with the Borneo Vortex and the Easterly Wave as the main factor that hinder the cold surge propagation to the south. Basides, the cold surge propagation will block the Inter Tropical Convergence Zone movement to north at the end of the rainfall season and sometimes force the ITCZ to moce back southward to the 10-15S thus will incite more convective activities and large precipitations in south Indonesia especially over Java during the rainfall period in western part of Indonesia.